InAs nanostructures on polar GaAs surfaces. (1st December 2008) - Dialynas, G.E.; Pantazis, A.; Hatzopoulos, Z.; Androulidaki, M.; Tsagaraki, K.; Konstantinidis, G.; Xenogianni, C.; Trichas, E.; Tsintzos, S.; Savvidis, P.G.; Pelekanos, N.T.
InAs nanostructures were grown by molecular beam epitaxy on GaAs (111)B and (211)B substrates at various growth temperatures between 450°C and 530°C. Their structural properties were studied by atomic force microscopy. For the (111)B grown nanostructures, the formation of self-aligned InAs quantum dashes was revealed, which in some cases took the form of nanowires. In the (211)B case, the shape and size of nanostructures is drastically affected by growth temperature. At lower growth temperatures, fabrication of quantum dots has been achieved by deposition of 2MLs of InAs. However, when the same amount of InAs was deposited at higher growth temperatures, a drastic change of nanostructure from dots to dashes occurred. Towards a better understanding of nanostructure properties, systematic photoluminescence (PL) measurements were performed on the (211) sample series. No PL emission related to quantum dash formation was observed, while a PL peak position at 1.27 eV was attributed to the (211)B InAs dots grown at 500°C. The PL peak blueshifted upon increasing the excitation intensity, an effect suggested to be related with the existence of strong piezoelectric field in the [211]B direction. The latter was also confirmed in micro-PL experiments through metallic apertures, where a negative biexciton binding energy was observed.